STATURE ESTIMATION FROM PARTIAL MEASUREMENTS AND MAXIMUM LENGTH OF UPPER LIMB BONES IN KOREANS - Lee, Je-Hun; Jeong, Young-Gil; Lee, Nam Seob; Han, Seung Yun; Han, Seung-Ho (International Journal of Research -GRANTHAALAYAH, 2015)
The aim of this study was to develop regression equations for stature estimation using the upper limb bone in Korean individuals. A total of 105 samples (55 men and 50 women) obtained from cadavers were used for developing equations. Bones with obvious pathologies or healed fractures were excluded. The coefficient of determination (r2) of the variables was slightly higher in men than in women. Ulna length (MLU) in both sexes was found to have the highest r2 value. Moreover, the regression equation using a stepwise analysis in a sample of combined sex using partial segments was based on MLR (Maximum length of the radius), MLH (Maximum length of the humerus) and TDHH (Transverse diameter of the humeral head) (r2 = 0.949). This method can be used to estimate stature when unidentified human bones are found at excavation sites.